PENGARUH METODE PEMBELAJARAN DAN PERSEPSI TENTANG LINGKUNGAN TERHADAP KEPEDULIAN TARUNA PADA PELESTARIAN LAUT - Siswanto, Hadi (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2017)
The research objectives are to determine the effect of learning method and environmental perception on awareness of marine conservation. The research was accomplished toward students of the Sekolah Tinggi Ilmu Pelayaran, Jakarta with factorial 2x2 design. The results are: (1) Awareness of marine conservation between on job trainning method and simulation training method have significant difference. (2) Students with higher of environmental perception, awareness of marine conservation between on the job training method and simulation training method have not significant difference. (3) Students with lower of environmental perception, awareness of marine conservation between on the job training method and simulation training method have not significant difference. (4) There is an interaction effect between learning method and environmental perception on awareness of marine conservation. Therefore, in enhancing students’ awareness of marine conservation, using learning method and by controlling environmental perception should be taken in consideration.